دور الشاهد في بناء القاعدة النحوية - البب, إبراهيم; حكمت, بربهان (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
Grammatical rules are deduced from Arabic spoken by ideally intuitive Arabic speakers, and illustration is the spirit of the rule, endowing it with life, pleasure, and originality. The Arabic used in illustration is that of the holy Quran, sayings of the Prophet as well as renowned poetic and prosaic statements by Arabs from the Jahileah period up to 150 Hizra,i.e, the end of the period of providing arguments. The term illustration is an original Arabic term that came out of Arab concern over mistakes in Arabic. The holy Quran is the source of illustrations, as it is the pillar upon which all other illustrations depend.This paper tries to study the relationship between the grammatical rule and illustrations as well as to demonstrate the motives for illustration, its mechanism, principles, and sources. It also tries to address some equivalents such as provision of argument and evidence as well as analogy.القواعد قوانين مستنبطة من كلام العرب الذين لم تفسد سلائقهم، والشاهد يمثل روح القاعدة، إذ يضفي عليها الحياة والمتعة والأصالة، والكلام العربي الذي يستشهد به هو القرآن الكريم والحديث النبوي الشريف وما أُثر من كلام العرب شعراً ونثراً منذ الجاهلية حتى نهاية عصر الاحتجاج. ومصطلح الشاهد مصطلح عربي أصيل ظهر نتيجة خوف العرب على لغتهم من اللحن، ويعد القرآن الكريم الأصل الأول للاستشهاد، فهو الدعامة التي ترتكز عليها مصادر الاستشهاد الأخرى.يحاول هذا البحث دراسة العلاقة بين القاعدة النحوية والشواهد، وإظهار دوافع الاستشهاد وطرقه وأركانه ومصادره، والوقوف عند بعض مرادفاته كالاحتجاج والاستدلال والتمثيل.